ANALISIS KONSEKUENSI INOVASI TUMPANGSARI .JERUK DAN PADI SAWAH DI KECAMATAN NGOMBOL KABUPATEN PURWOREJO - Dwiningtyas Padmaningrum; Emi Widiyanti (Universitas Sebelas Maret, 2003)
The research is purpose to know characteristic farmer intercropping for orange and rice field also know consequence of this inovation farmer who adopt of intercropping technology and rice.fie/cl in Purworejo regency. The research used basic method analysis description and survey technology. Population in this research is.farmer who adopt intercropping orange and rice field.Taking sample is held snow ball method, as much as 30 responden. Analysis also hold with frequency tabulation analysis also description analysis. Thought framework of research there are chage as result or consequency adopt of inovation intercropping orange and rice field can form consequency which is wanted or not. The consequence can be judgment by farmer to continuen or stop of the adopt. Result of research can be knew that consequeny which is deliveredrespondence are increase income and increase in the skill cultivation in horticultural plants, special orange, while the field or work for family have too large of area, but the production of rice field and fertility ofthe farmland is the same, but this intercropping also giving other consequence which is worsen enough, certain financial capital which is preparedfhr means of increasing production andfree time for farmer is subsided